Synthesis and Physical-Chemical Properties of 5-Phenethyl-4-R-4Н-1,2,4-triazole-3-thioles and Their Chemical Transformations - Ihnatova, T. V.; Kaplaushenko, A. G.; Frolova, Yu. S.; Ігнатова, Тетяна Вікторівна; Каплаушенко, Андрій Григорович; Фролова, Юлія Сергіївна (My University, 2018)
Great value for pharmacologists is the synthesis of new triazole derivatives as they have medicinal importance and are found to be used in a variety of pharmacological preparations. 1, 2, 4-triazole derivatives were reported to possess diverse biological activities, such as antimicrobial, antifungal, antitumor, anti-inflammatory, ant tuberculosis and herbicidal properties. The purpose of our research is the synthesis of new highly effective and low-toxic substances, namely of 5-phenethyl-4-R-4H-1,2,4-triazole-3-thioles and their derivatives, the establishment of physical and chemical properties of all synthesized compounds. For synthesized of 5-phenethyl-4-R-4H-1, 2, 4-triazole-3-tioles at first was esterifies butyl ester of hydrocinnamic acid, then with hydrazine hydrate was given hydrazide 3-phenylpropanoate. Further was received carbotiamids and in the last step was gotten 5-phenethyl-4-R-4H-1,2,4-triazole-3-tioles.2-((5-phenethyl-4-R-4H-1,2,4-triazole-3-yl)thio)nitriles were received by adding appropriate halogen nitriles to 5-phenethyl-4-R-4H-1,2,4-triazole-3-tioles in alkaline-alcohol environment. During the experiment 11 synthetic studies of novel compounds was obtained, which have not been described previously. The structure of received compounds, namely 5-phenethyl-4-R-4H-1,2,4-triazole-3-tioles and 2-((5-phenethyl-4-R-4H-1,2,4-triazole-3-yl)thio)nitriles has been confirmed by elemental analyze, infrared and chromatography-mass spectrometry was confirmed by elemental analysis, infrared and chromatographic mass spectrometry, which fully confirmed their composition. The results confirmed the structure of the synthesized compounds, which indicates the possibility of their further use in biological studies.
Keywords: 1, 2, 4-triazoles; synthesis; physical-chemical properties; transformation